Defining the Field of Sequence‐Controlled Polymers - Lutz, Jean‐François (Macromolecular rapid communications., 2017)
Over the last ten years, the development of synthetic polymers containing controlled monomer sequences has become a prominent topic in fundamental and applied polymer science. This emerging area is particularly broad and combines classical polymer chemistry tools with techniques imported from other domains such as biology, biochemistry, organic synthesis, engineering, and bioanalytics. Consequently, it also generates new structures, terminologies, and applications that are not within the traditional scope of polymer science. The term “sequence‐controlled polymers” (SCPs) was recently proposed as a generic name to describe all these recent trends. However, since the field of SCPs has been growing very rapidly in recent literature, it is urgent to accurately define its scientific frontiers. In this important context, this review is an attempt to define, rationalize, and classify the field of SCPs. In particular, all synthetic approaches that have been reported for the synthesis of SCPs are discussed and categorized. In addition, the characterization tools, properties, and potential applications of these new polymers are described herein. Overall, this review serves as a reference guide for understanding the burgeoning field of SCPs. The field of sequence‐controlled polymers is an exciting emerging area that combines classical polymer science aspects with concepts imported from other disciplines. In this context, the aim of this review is to help the readers understand this young, yet fast‐moving area of research. Thus, the state‐of‐the‐art is described. Additionally, some definitions and categories are also proposed for rationalizing the field.